Contributions towards decision support for site-specific crop management: a study of aspects influencing the development of knowledge-intensive differential management decisions. - OLIVEIRA, R. P. de (2009)
The thesis Preface first introduces the overall research context of Precision Agriculture (PA) and the specific aims of this work. Aims are particularly related to aspects of the opportunity for the adoption of Site-Specific Crop Management (SSCM) technology, which underline assumptions of efficient production management and environmental-economic principles. The body of the investigation is structured in three parts concerning the background information on Decision Support Systems (DSS) for SSCM, the proposal of methods supporting SSCM decisions, and the general impact of this work with appendices. A historical data set (1996-2006) of yield monitoring, crop reflectance imagery and soil electrical conductivity (ECa) was gathered from 80 broad-acre grain crop fields across three agronomic regions in Australia. These are 5 farms in South Australia, 3 in the Riverine and 8 in Northern New South Wales, which form part of a non-profit growers network built on the cooperative sharing of information and experience on the promotion, development and adoption of PA as a means for profitable and sustainable farming. In total, 218 field-year samples over a decade of intensive monitoring include several grain crops.